The Iceberg Theory: A Critical Reading of A.A Milne’s Tale Winnie The Pooh (1926) - Alkahlan, Hessa; Al-Dossari, Afnan; Al-Qahtani, Leena (International Journal of Language and Literary Studies, 2020)
The paper tackles Earnest Hemingway’s theory “The Iceberg Theory”, with an emphasis on the omission technique, through which the tip of the Iceberg is seen; omitting what is underneath the surface, the undetected mass. The study examines the possible influence of Edgar Allan Poe, who is known to be conscious of the "Theory of Omission" before Hemingway. Sigmund Freud’s psychological perspective, as well, for he studied the different levels of the unconscious entity of his patients. The research concludes with an analysis of the life of A.A Milne and his tale “Winnie the Pooh”, its characters’ true nature, and a possibility of each one of them having underlying purposes unintentionally set by the author to represent different psychological disorders.